Analisis Pelatihan, Beban Kerja, Dan Supervisi Kepala Sekolah Terhadap Kinerja Guru Sekolah Dasar - Siswanto Siswanto (CV. Aksara Global, 2023)
The purpose of this study was to analyze the extent to which Workload, Training, and Principal Supervision influence the improvement of teacher performance in the online learning process. The population and samples taken in this study amounted to 26 teachers at SDN Sukasari 6 Kota Tangerang with a saturated sampling technique. Data collection uses primary data through distributing questionnaires. The data analysis technique used is a descriptive, internal data analysis technique through the Smart Partial Least Square (PLS) 3.0 application. The results of the study show that workload and training have a positive and significant effect on teacher performance. Likewise, the same thing with the Principal's Supervision has a positive and significant effect on the performance of teachers at SDN Sukasari 6 Tangerang City. This research provides input to all elementary schools to take into consideration regarding online learning which has an impact on increasing the ability of teachers to apply it so that educational goals are achieved effectively and efficiently.